Paddy industry and paddy farmers well-being: a success recipe for agriculture industry in Malaysia - Fahmi, Zaim; Abu Samah, Bahaman; Abdullah, Haslinda (Canadian Center of Science and Education, 2013)
Paddy is an important crop in Malaysia and it is vital for the nation's food security. Apart from this, the statistic also has proven that paddy industry in Malaysia has generated stable income for the country. Such income generation has reflected the success of this industry. Nonetheless, is the success of this industry has any impact on the paddy farmers particularly on their well-being? This query has become the main objective of this paper which is to discover the impingement factors of paddy farmers’ well-being. This is qualitative study where data were gained from documents and literature analyses. Based on the analyses performed, it can be seen that factors such as financial, social and human should be considered to further enhance the farmers’ well-being.